Effect of internal control systems, implementation of good governance and employee competence on financial management performance - Epa, Epa; Badruzaman, Jajang; Supriadi, Apip (Institute of Computer Science (IOCS), 2024)
Improper financial management performance can cause problems. Problems of governance, development, guidance and empowerment and unplanned financing, not properly organized and disciplined budgets as regulated by the Ministry of Finance. The purpose of this study is to determine and analyze the effect of the Internal Control System, Implementation of Good Government Governance and Employee Competence on Financial Management Performance in Developing Villages in Tasikmalaya Regency based on the Decree of the Director General of Village and Rural Development No. 389.4.1/2021. The method applied was a survey with a quantitative approach. The sample used was 156 developing villages in Tasikmalaya Regency which were determined by proportionate stratified random sampling. The analysis technique uses path analysis and the results indicate that the internal control system, implementation of good government governance and employee competence simultaneously and partially have a positive and significant effect on financial management performance in developing villages in Tasikmalaya.